Handbook on Craniofacial Superimposition The MEPROCS Project - Damas, Sergio (Springer Nature, 2020)
This open access handbook presents a trustable craniofacial superimposition methodological framework. It includes detailed technical and practical overviews, and discussions about the latest tools and open problems, covering the educational, technical, ethical, and security aspects of this forensic identification technique. The book will be of particular interest to researchers and practitioners in forensic anthropology and forensic ID, and also researchers in computational intelligence. It is the final result of a European project, New Methodologies and Protocols of Forensic Identification by Craniofacial Superimposition (MEPROCS). The project collaborators who contributed to this handbook are: S. Damas, O. Ibáñez, M.I. Huete, T. Kahana, C. Wilkinson, E. Ferguson, C. Erolin, C. Cattaneo, P.T. Jayaprakash, R. Jankauskas, F. Cavalli, K. Imaizumi, R. Vicente, D. Navega, E. Cunha, A.H. Ross, E. Veselovskaya, A. Abramov, P. Lestón, F. Molinero, E. Ruiz, F. Navarro, J. Cardoso, F. Viegas, D. Humpire, R. Hardiman, J. Clement, A. Valsecchi, B.R. Campomanes-Alvarez, C. Campomanes-Alvarez, A.S. Çağdır, T. Briers, M. Steyn, M. Viniero, D.N. Vieira, and O. Cordón. ; Authors among leading researchers and practitioners worldwide Reports successful collaborative project results First comprehensive guide on this important technique Open Access